La relación organismo-mecanismo: un problema de la controversia Leibniz-Stahl - Duchesneau, François (2014)
The organism-mechanism relationship is at the center of the controversy between Leibniz and Stahl. Leibniz borrowed his notion of organism from Hoffmann who had established a mechanistic theory of living beings, based on the teleological disposition of complex organic structures that a system of inner forces activates. Inspired by that model, Leibniz criticizes Stahl’s conception of the soul as an agent and regulator of vital motions. He develops in contrast his views on the physiological autonomy of the organic body, governed by laws of change that parallel those ruling over of the soul’s per- ceptions and appetites.